2022
DOI: 10.13057/biodiv/d230655
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Sclerotinia minor attack on pyrethrum plants by Trichoderma harzianum in glasshouse experiment

Abstract: Abstract. Ramona Y, Darmayasa IBG, Line MA. 2022. Biological control of Sclerotinia minor attack on pyrethrum plants by Trichoderma harzianum in glasshouse experiment. Biodiversitas 23: 3264-3269. The aim of this research was to elucidate the efficacy of Trichoderma harzianum (isolate Td22) grown in a ratio of 2:8 millet seeds and wood fiber waste (WFW) compost mixture to suppress Sclerotinia minor infection in pot trails on the pyrethrum plants (in 0.5 L pots). The pots were filled with soil and mixed with Td… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Its indicating that rP6281 may be developed as an effective anti-mold agent for fruit storage. Ramona et al (2022) also reported that T. harzianum (Td 22 isolate) was able to suppress Sclerotinia minor infection of Pyrethrum plants.…”
Section: Introductionmentioning
confidence: 94%
“…Its indicating that rP6281 may be developed as an effective anti-mold agent for fruit storage. Ramona et al (2022) also reported that T. harzianum (Td 22 isolate) was able to suppress Sclerotinia minor infection of Pyrethrum plants.…”
Section: Introductionmentioning
confidence: 94%
“…The rhizobacteria increase root growth and plant height and protect plants from diseases caused by soil-borne pathogens (El-Kafrawy, 2008;Soylu, 2011;Imriz et al, 2014;Abdeljalil et al, 2016;Sen et al, 2016). Many studies have been conducted on the biological control of S. sclerotiorum or S. minor, and the causative agent of white rot on lettuce (Budge and Whipps, 2001;Fiume and Fiume, 2005;Rabeendran et al, 2006;Chitrampalam et al, 2008;Villalta et al, 2012;Baniasadipour and Shahidi Bonjar, 2014;Elias et al, 2016;Yıldız and Cenberci-Coskun, 2017;Soylu et al, 2021;Ramona et al, 2022). The studies reported that Coniothyrium minitans, Trichoderma harzianum, and Gliocladium spp.…”
Section: Introductionmentioning
confidence: 99%